Description of Sociodemography and Disease Distribution of Pilgrims through Wukuf Safari In The Hajj Period 1443H/2022M - Syahruddin, Maslim; Ridho, Sayid; Tyastuti, Dwi (The Avicenna Medical Journal, 2024)
Background: Hajj is wukuf at Arafah, which distinguishes it from Umrah.. The Indonesian government as the hajj organizer is obliged to facilitate wukuf safaris for pilgrims who have physical limitations or suffer from illness with assistive devices. Meanwhile, study on Hajj Health during Wukuf at Arafat and its relation to the condition of the pilgrims who carry out Safari Wukuf is still very limited. Therefore, this study aims to describe the disease and sociodemographic factors in Wukuf safari pilgrims during the 1443H/2022M Hajj period.Method : This study was carried out as a descriptive study using secondary data from 1443H/2022M Hajj pilgrims in the SISKOHATKES application. This research includes  138 pilgrims who participated in wukuf safari. The data is processed using descriptive analysis. The ethical clearance was obtained from the UIN Syarif Hidayatullah Jakarta Ethical Committee (Number No.B-022/F12/KEPK/TL.00/04/2023).Result : This study included 138 pilgrims from 12 embarkation points, with the majority coming from East Java (27 respondents) and West Java (25 respondents). The elderly (60-70 years) made up 59.4% of respondents, and those from the first batch (arrived in Medina to Mecca) made up 65.2%. All respondents have comorbidities, with cardiovascular illness (77.5%) and endocrine diseases (73.2%) being the most common. Cardiovascular illnesses are found to be the most prevalent among pilgrims in this study.Conclusion : The pilgrims who undergo Safari Wukuf are those who have a comorbid. Most diseases are caused by cardiovascular and endocrine disorders in the elderly congregation (60-70 years) and on the departure of the first wave.